An analysis of predictors of history content knowledge: Implications for policy and practice - Fitchett, Paul G.; Heafner, Tina L.; Lambert, Richard G. (Education Policy Analysis Archives, 2017)
How and to what extent students learn history content is a complicated process, drawing from the instructional opportunities they experience; the policy prioritization of history/social studies instruction in schools; and their own cultural perspectives toward the past. In an attempt to better understand the complex inter-play among these dimensions, we examined relationships among student sociocultural characteristics, instructional exposure, and school-level variables and US History content knowledge. Using data from the 2010 National Assessment of Educational Progress Test on US History (NAEP-USH), multilevel analyses indicated that while sociocultural indicators (such as race, gender, and socioeconomic status) correlate with achievement, students’ instructional exposure variables remain significant predictors of history content knowledge. Moreover, school context such as building-level demographics and state testing-policy predict between school variance in content knowledge and moderate the achievement gap. Results also suggest that, while a substantial achievement gap remains, exposure to text-based instructional practices is associated with increased knowledge. Findings from this study have policy implications for the development of a more inclusive social studies curriculum, the advocating of text-dependent instruction as a high-leverage practice among history teachers, and cautious consideration of tests as proxies for accountability in history education.